Smanggi Berbatik Collaborative Workshop in Scientific Writing Training Activities for Students of SMAN 1 Sragi - Sumargono Sumargono; Rinaldo Adi Pratama; Yusuf Perdana (The Future of Education Journal, 2026)
The knowledge of both teachers and students regarding the writing of scientific papers, whether related to natural phenomena, history, or local wisdom in Lampung, is still very lacking. This could be due to the fact that the majority of educators and students are still focused on formal learning activities, while improving scientific writing skills has not yet become a priority for students at SMA N 1 Sragi in the Sragi District. The main objective of this service is to educate high school students thru the collaboration of Kombel "SMANGGI BERBATIK" SMA N 1 Sragi, which can create synergy between the needs of students and the resources available at the school. Based on the analysis of the workshop activities of the Kombel Smanggi Berbatik collaboration in the scientific writing training for SMA N 1 Sragi students, the average pre-test score of the participants was 65.6, and the average post-test score was 83.6. Overall, the percentage increase in the evaluation results from the pre-test to the post-test was 21.5%. This percentage increase indicates that the Kombel Smanggi Berbatik collaboration workshop in the scientific writing training for SMA N 1 Sragi students was effective. Thru this workshop, students can develop their potential in creating engaging and innovative scientific writings.